How different are the alternative economic policy uncertainty indices? The case of European countries - Jaromir Baxa; Tomáš Šestořád (Charles University in Prague, Institute of Economic Studies (IES), 2024)
Several alternative news-based Economic Policy Uncertainty indices have been developer for Spain and a few other European countries. These alternative indices differ in the selection of keywords, newspaper coverage, and a scaling factor that is used to calculate the EPU index from the raw news data. Using the generalized forecast error variance decompositions of the time-varying parameter VAR model and the analysis of dynamic connectedness, we show that the restriction to include only domestic news affects estimated spillovers substantially, leading to different qualitative and quantitative assessments of uncertainty spillovers in Europe. Therefore, not all EPU indices are the same.
Keywords: C32; F42; F45; 330; Uncertainty; Forecast error variance decomposition; Spillovers